Attitudes toward Animals of Students at Three European Veterinary Medicine Schools in Italy and Spain. (4th May 2019) - Menor-Campos, David J.; Diverio, Silvana; Sánchez-Muñoz, Carolina; López-Rodríguez, Rocío; Gazzano, Angelo; Palandri, Lorenzo; Mariti, Chiara
ABSTRACT: The European Veterinary Code of Conduct recognizes the crucial role of veterinarians in improving animal welfare and maintaining its standards. However, several studies have claimed that veterinary students' attitudes toward animals may worsen as they progress through their academic training. This study aimed to investigate students' attitudes toward nonhuman animal use in three European veterinary medicine schools (Italy and Spain). For this purpose, 565 veterinary students completed a questionnaire consisting of a range of items grouped into four animal-use categories: "Research, " "Entertainment, " "Utilitarianism, " and "Veterinary Issues." Items were scored on a 5-point Likert-type scale, with higher scores indicative of higher concern regarding animal welfare. Results showed that the use of animals for "Entertainment" and questions related to "Veterinary Issues" raised the most concern among the veterinary students, while the use of animals for "Research" was of least concern. Moreover, we also examined some potentially confounding factors: age, academic year (first to fifth), gender, previous experience with pets, and university. Female students had a higher concern for animal welfare compared with their male counterparts. Students in their earlier stages of training as veterinarians also exhibited a greater concern for animal welfare compared with those of later academic years. Other factors affecting students' attitudes toward animal use were the age of the students and the university they were enrolled at. The findings of this study confirm that attitudes toward animal use are not homogeneous and are associated with students' demographic, educational, and personal characteristics.